If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 2 + -5x = 2x + -1(-2 + -1x) Reorder the terms: 2 + 8x + -5x = 2x + -1(-2 + -1x) Combine like terms: 8x + -5x = 3x 2 + 3x = 2x + -1(-2 + -1x) 2 + 3x = 2x + (-2 * -1 + -1x * -1) 2 + 3x = 2x + (2 + 1x) Reorder the terms: 2 + 3x = 2 + 2x + 1x Combine like terms: 2x + 1x = 3x 2 + 3x = 2 + 3x Add '-2' to each side of the equation. 2 + -2 + 3x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 0 + 3x = 2 + -2 + 3x 3x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 3x = 0 + 3x 3x = 3x Add '-3x' to each side of the equation. 3x + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| (23)*x+10=(x5)+(365) | | 12x-5+9=-5 | | 8.1x+2.3=5.1x-3.1 | | 4-2(x+1)=3(2x-1)-8x+5 | | 2x^2-11x*5=0 | | 3x+7/2=2 | | 8=4(m-2)+4 | | 5m+=3m+9 | | 7x^2=105 | | 42=(2*7)+2w | | -7a=-12-65 | | 7y-7=5y+3 | | 12.5x+(7.2x)=21.2 | | 4x^2+38+70=0 | | 42=14+2w | | 3x-(2x-10)=6x | | 4x+4+3x=52 | | 4y^2-48y=112 | | 0.34*y-0.2=0.15*y+0.1 | | 3(x-5)=8x-30 | | 4y^2-48y-112=0 | | 12x-5x+9=-5 | | 2x-4.5=0.5(x+3) | | 4x-6=5x+5 | | x-3.6=-10.2-3.2 | | 4+9x=7x+3+2x | | 4x-3.6=2x-4.8 | | 5(x+2)+2x=80 | | x+7(-1)=0 | | 14a^5+85a^3b^2+6ab^4= | | -6w=78 | | 45x+6x=55-4 |